Black swan [videorecording (Blu-Ray)] - Aronofsky, Darren; Heyman, Mark, 1979-; Heinz, Andrés; McLaughlin, John J.; Medavoy, Mike; Messer, Arnold W.; Oliver, Brian, 1971-; Franklin, Scott; Portman, Natalie, 1981-; Cassel, Vincent, 1966-; Kunis, Mila, 1983-; Hershey, Barbara, 1948-; et al. (20th Century Fox Home entertainment, 2011)
A psychological thriller set in the world of New York City ballet. An insecure ballet dancer wins the lead in Swan Lake but slowly loses her grip on sanity when a seductive newcomer is out to steal her role.